Rewind this! [videorecording (DVD)] (FilmBuff, 2013)
In the 1980s, videotape changed the world and laid the foundation for modern media culture. This film traces the rise and fall of VHS from its heyday as the mainstream home video format to its current status as a nostalgic relic and prize to collectors who still cherish it. Features interviews with both filmmakers and enthusiasts from the VHS era.